The Cahokian Crucible: Burning Ritual and the Emergence of Cahokian Power in the Mississippian Midwest. Issue 3 (July 2019) - Baltus, Melissa R.; Wilson, Gregory D.
Abstract : Much of what is known about the Indigenous city of Cahokia, located in and influential on the North American midcontinent during the eleventh through fourteenth centuries AD, derives from decades of salvage, research, and CRM excavations in the surrounding American Bottom region. We use this robust dataset to explore patterns of building conflagration that suggest these practices of burning were part of pre-Mississippian traditions that were bundled into new Cahokian landscapes during the early consolidation of the city. These bundled practices entangled sources of power that were at once political and religious, thus transforming the practices and meanings associated with terminating building use via fire. Abstract : Mucho de lo que se conoce sobre la ciudad indígena de Cahokia, ubicada en el medio continente norteamericano durante los siglos XI al XIV dC, deriva de décadas de excavaciones de rescate, investigación y CRM en la región circundante de América. Utilizamos este sólido conjunto de datos para explorar patrones de conflagración de edificios, lo que sugiere que estas prácticas de quema fueron parte de las tradiciones pre-Mississippian que se incluyeron en los nuevos paisajes de Cahokian durante la consolidación temprana de la ciudad. Estas prácticas agrupadas enmarañaron fuentes de poder que eran a la vez políticas y religiosas, transformando así las prácticas y los significados asociados con la terminación del uso del edificio a través del fuego.